Kondisi Kualitas Sanitasi dan Kebersihan di Pasar Panjang, Kecamatan Wua Wua, Kota Kendari - Karimuna, Sitti Rabbani; Taufik, Aliyyah Nisrina; Taoha, Aurel Amelia Putri; Tiara, Intan; Masaid, Femy Febriyanti; Artanty, Andi Anindyah; Mutmainna, Aulia; Safitri, Selvi; Azyuyun; Ferniati; Sasono, Ihsan Adi (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The market is a meeting place between traders and buyers, which is often visited by the community and has the potential to become a location for disease transmission through vectors. This community service uses observation methods with checklist forms, interviews, and counseling for traders. The results show that market sanitation, including water, air, soil, and food, has not met the expected standards. Improvements are needed, especially in waste management, toilet facilities, and clean water provision. The average sanitation quality score of the six parameters showed significant deficiencies. Counseling was conducted to educate traders about efforts to improve market sanitation. This community service emphasizes the importance of effective sanitation management to improve public health and prevent the spread of disease. It is hoped that improvements in sanitation infrastructure and education for traders can improve the cleanliness conditions at Panjang Market, Wua-wua District, Kendari City.